Morocco’s international crossroads, a stumbling block for liberals and authoritarians (1912-1926) - La Porte, Pablo (Hispania Nova, 2021)
Spanish colonial interests in Morocco were constrained by the international balance of power held by Britain and France in the Western Mediterranean. Spanish ambitions in Morocco were also hampered by local rivalries with her colonial neighbour, France, which determined the problematic nature of the Spanish colonial project and, ultimately, its enduring and negative effects on the Peninsula.
Keywords: Spanish Protectorate; Morocco; colonialism; Rif War (1921-1926)